2007
DOI: 10.1158/1055-9965.epi-06-1008
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Osteopontin in Tumor Progression and Metastasis in Breast Cancer

Abstract: The use of cancer biomarkers to anticipate the outlines of disease has been an emerging issue, especially as cancer treatment has made such positive steps in the last few years. Progress in the development of consistent malignancy markers is imminent because advances in genomics and bioinformatics have allowed the examination of immense amounts of data. Osteopontin is a phosphorylated glycoprotein secreted by activated macrophages, leukocytes, and activated T lymphocytes, and is present in extracellular fluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
147
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(159 citation statements)
references
References 179 publications
(200 reference statements)
6
147
2
4
Order By: Relevance
“…Although the mechanisms involved in the fibroblast responses remain obscure, the possibility that they are coordinated through interactions with ECM proteins is increasingly appreciated. OPN is a pleiotropic matricellular protein that is known to be involved in an array of biological processes including remodeling, metastasis, scarring, and inflammation (4,7,40,41,43,61). Several in vivo and in vitro studies suggested an important role of OPN in mesenchymal cell proliferation in vascular remodeling (31,32,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms involved in the fibroblast responses remain obscure, the possibility that they are coordinated through interactions with ECM proteins is increasingly appreciated. OPN is a pleiotropic matricellular protein that is known to be involved in an array of biological processes including remodeling, metastasis, scarring, and inflammation (4,7,40,41,43,61). Several in vivo and in vitro studies suggested an important role of OPN in mesenchymal cell proliferation in vascular remodeling (31,32,37).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are abundantly expressed during development; however, in adulthood their production is mainly restricted to wound healing and tissue remodeling (7,25,34,36). Among these proteins, OPN is currently receiving the most attention in cancer and tissue repair (7,43,61). OPN was first described as a phosphoprotein secreted by malignant epithelial cells (50) but has now been shown to be secreted by many cell types, including osteoclasts, lymphocytes, macrophages, vascular smooth muscle cells, and cancer-associated fibroblasts.…”
mentioning
confidence: 99%
“…Full length OPN pre-mRNA consists of 7 exons (Rodrigues et al 2007) while OPN-b lacks exon 5 and OPN-c lacks exon 4 (Hijiya et al 1994;Kiefer et al 1989;Saitoh et al 1995;Young et al 1990) (Fig. 1).…”
Section: Opn Splice Variants/isoformsmentioning
confidence: 99%
“…In human malignant melanoma, OPN expression is significantly associated with reduced relapse-free survival and additional histological parameters that are associated with poor clinical outcome [7,24,29,33]. OPN is a prognostic marker in a variety of cancers [30,[39][40][41]. In metastatic and primary melanomas, OPN has also been suggested to be a novel promising biomarker for the detection of metastases in patients with primary melanomas [24,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that OPN protein is overexpressed in the majority of human cancers, including malignant melanoma, and is associated with tumor progression [14,[23][24][25][26][27][28][29][30]. Extensive microarray analyses of melanomas demonstrated that OPN also plays a role in melanoma progression [14,28,31,32].…”
Section: Introductionmentioning
confidence: 99%